Ketrampilan Membaca pada Pembelajaran Bahasa Indonesia di SD/MI - Suparlan Suparlan (FONDATIA, 2021)
Language is a system, meaning that the language is formed by a component that is permanently patterned and can be explored. As a system, language is not only systematic but also systemic. By systemic, it means that the language is arranged according to a certain pattern, not arranged randomly or carelessly. Whereas systemic means, the language system is not a single system but consists of subsystems. The ability to read skills is a very important skill in life, not only important in educational life, but also very important in social life. By reading students will know more about everything, students will also have broader knowledge and insights. Reading skills are the main capital of students. With this ability, students can learn other sciences, can communicate their ideas and be able to express themselves.